PERAN DIVIDEND POLICY DALAM MEMODERASI PENGARUH LIQUIDITY, FIRM SIZE, EARNINGS QUALITY, DAN PROFITABILITY TERHADAP FIRM VALUE - Hansel Veriant Simon; Sapto Jumono (JURNAL LENTERA AKUNTANSI, 2026)
This study aims to analyze the role of dividend policy in moderating the influence of liquidity, firm size, earnings quality, and profitability on firm value in food & beverage subsector companies listed on the Indonesia Stock Exchange, using Signalling Theory and Bird in the Hand Theory as the theoretical foundation. A quantitative approach was employed using secondary data in the form of financial statements published on the Indonesia Stock Exchange website. The research sample was determined through purposive sampling and analyzed using Moderated Regression Analysis (MRA). The results show that firm size, profitability, and dividend policy contribute to increasing firm value, while liquidity and earnings quality have not become determining factors in the formation of firm value. In the interaction testing, dividend policy only strengthens the relationship between firm size and firm value, but does not strengthen the relationship between liquidity, earnings quality, or profitability and firm value. These findings indicate that in the food & beverage subsector, the market responds more strongly to company scale and the ability to generate profits as primary signals of performance and business prospects, while dividend policy functions as a value enhancing factor, particularly for companies with large size and established business positions.